Práticas pedagógicas e autismo: o que as pesquisas revelam? - Bernardes, Kamylla Ribeiro (Universidade Federal de São Carlos, 2024)
The present study is characterized as a bibliographic review that addresses works produced on pedagogical practices and their relationship with autism. Its purpose is to reflect on pedagogical practices aimed at promoting the inclusion and academic and social development of children with ASD. By sharing this journey, I aim to contribute to the constant improvement of inclusive education, highlighting the importance of reframing pedagogical practices to meet the specific needs of students with autism. Data collection for this research was carried out through a systematic search in virtual libraries and institutional repositories. The research addresses the barriers faced by educators in implementing inclusive practices, emphasizing the lack of awareness of the importance of inclusion and the shortage of multiprofessional qualification. Among the analyses of challenges and possibilities reported in the investigated research, it is highlighted that collaborative partnership between teachers, health professionals, and families plays a crucial role in creating a welcoming and productive learning environment for autistic students. Reflection onpedagogical practices addressed in this work aims to promote the inclusion and academic and social development of children with ASD. The importance of reframing pedagogical approaches to meet the specific needs of students with autism is the necessary path to building a more inclusive and egalitarian education.
Pedagogical practices and autism: what does research reveal?
Keywords: Práticas Pedagógicas; Autismo; Inclusão; TEA; Educação Inclusiva; Pedagogical Practices; Autism; Inclusion; ASD; Inclusive Education; CIENCIAS HUMANAS::EDUCACAO